Border, Border, Wide and Far, How We Wonder What You Are - Wei, Shang-jin, 1964- 1964- (The World Bank, 1999)
November 1999 - Crossing national borders adds significantly to price dispersion. This study of prices in Japan and the United States finds that a substantial part of that border effect is attributable to distance, shipping costs, exchange rates, and relative variability in wages. Parsley and Wei exploit three-dimensional panel data on prices for 27 traded goods, over 88 quarters, across 96 cities in Japan and the United States, to answer several questions: · Does the average exchange rate between countries stray further from zero than that between cities within a country? · Is there any tendency for the average exchange rate to move closer to zero over time? · Does the border narrow over time? · Is there evidence linking changes in the so-called border effect - the extra dispersion in prices between cities in different countries beyond what physical distance could explain - with plausible economic explanations, such as exchange rate variability? The authors present evidence that the intranational real exchange rates are substantially less volatile than the comparable distribution of international relative prices. They also show that an equally weighted average of commodity-level real exchange rates tracks the nominal exchange rate well, suggesting strong evidence of sticky prices. Next they turn to economic explanations for the dynamics of the border effect. Focusing on the dispersion of prices between city pairs, they confirm previous findings that crossing national borders adds significantly to price dispersion. Based on their point estimates, crossing the U.S.-Japan border is equivalent to adding between 2.5 and 13 million miles to the cross-country volatility of relative prices. They infer that distance, exchange rates, shipping costs, and relative variability in wages influence the border effect.